Clinical Assessment and Emergency Management of Pediatric Skull Fractures - Almazyad, Abdulrahman Mohammed Abdulrahman; Eisa Ali T. Alenazi,; Sultan Mukhlid Nazil Al-Anazi,; Faisal Jazzaa Muhammad Al-Anazi,; Faleh Eid Faleh Alruwaili,; Abdulrhman Mouhsen Ali Al-Shammari,; Farih Bustan Alruwaili,; Zaid Ayash Madhi Alruwaili,; Abdulelah Saad Alsaleem,; Abdulraman Jawad Jawdat Rasheed,; Talal Ali Alsharari,; Aqla Mottleb Hamoud Alhazm,; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Pediatric skull fractures are a common consequence of head trauma, with a high incidence in emergency settings. The unique anatomical and biomechanical properties of the developing skull, such as its thinness and pliability, influence fracture patterns and increase the risk of associated intracranial injury. Etiologies range from accidental falls to non-accidental trauma, necessitating a high index of suspicion in young children. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review aims to detail the clinical assessment, diagnostic evaluation, and emergency management principles for pediatric skull fractures, emphasizing a systematic, evidence-based approach and the critical role of multidisciplinary care. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive synthesis of current literature and clinical guidelines is presented, covering epidemiology, pathophysiology, and standardized evaluation protocols. The use of clinical decision rules (e.g., PECARN) to guide imaging, primarily non-contrast head CT, is discussed. Management strategies from initial Advanced Trauma Life Support (ATLS) stabilization to definitive neurosurgical intervention are outlined. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Most simple, linear skull fractures can be managed conservatively with observation. Neurosurgical intervention is indicated for depressed fractures (>5 mm), open fractures, fractures with dural violation (CSF leak), associated intracranial hematomas, and growing skull fractures. A thorough evaluation must always consider the possibility of abusive head trauma, especially in infants. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Successful management of pediatric skull fractures requires rapid primary assessment, judicious use of imaging guided by clinical decision rules, and a tailored approach to intervention based on fracture type and associated injuries. Outcomes are optimized through coordinated, interprofessional teamwork involving emergency medicine, neurosurgery, pediatrics, and child protection services.